شريعة القرآن علاج لمشكلات الإنسان: قراءة في فكر محمد عبد الله درازفي الإعجاز التشريعي للقرآن - Jauhar Ridloni Marzuq (TSAQAFAH, 2017)
Although sophisticated discoveries in the feld of science and technology have been found, human beings are still continuing to face the problems of life, such as injustice, social imbalance, arbitrariness, and greed. They forget that religion is still needed to solve these problems. In Islam, al-Qur’an and its teachings are the answer for these problems. This article tries to prove it through an analyzing Muhammad Abdullah Diraz’s thought. As a Muslim scholar, Diraz is able to integrate Islamic and Western knowledge. His thoughts have a strong characteristic in combining the naqli and aqli, fqh nas} and fqh wâqi’. According to Diraz one of the miracles of the Qur’an is that its sharias are not owned by other rules, in terms of methods, concepts, and contents. One of the main points of miracles of the Qur’anic laws is its ability to unify the two things that always contradict. The laws of the Qur’an are gentle but frm, fair but loving, simple but ﬂexible, idealistic but realistic. All combined in a suitable and balanced portion. These features are what Diraz attempts to present in his studies of al-Qur’an. Diraz’s theory is very appropriate to be a foothold in offering the laws of al-Qur’an to the people of the world who are in confusion looking for a way out of their problems.